Perancangan Sistem Informasi Administrasi Rukun Tetangga Berbasis Web Menggunakan Metode Scrum - Miranty Yudistira; Dedy Setiawan; Ari Andrianti; Devi Listiani Safitri; Zikra Zana; M. Sakti Guruh Pratama (CV. Graha Mitra Edukasi, 2026)
The manual management of population administration at the Rukun Tetangga (RT) level causes significant inefficiencies, including slow data retrieval, physical document duplication, and a lack of transparency in social assistance distribution. This study aims to design and implement a web-based RT administration information system named BISAKELOLA at RT 14, Kenali Asam, Jambi City, which integrates resident data management and social assistance management into a single platform. The system was developed using the Scrum method through three iterative sprints, with data collected through direct observation, interviews, and literature review, and validated using Black Box Testing based on the Equivalence Partitioning technique. BISAKELOLA successfully centralized resident data, accelerated information retrieval, eliminated physical document duplication of family cards and identity cards, and digitalized the social assistance submission process into a more transparent workflow. All test scenarios across four main modules, namely authentication, resident data, social assistance, and account management, performed as expected without critical errors. Sprint reviews conducted at the end of each sprint proved effective in adaptively accommodating user requirement changes, resulting in a system that is functionally aligned with real community needs. BISAKELOLA proves to be an effective digital solution for modernizing RT administrative services and improving social assistance transparency, and is expected to serve as a replicable model for community-level digitalization across other RT/RW environments in Jambi City.